CarotidSCORE.RU — risk stratification for complications after carotid endarterectomy - A. N. Kazantsev; D. D. Khasanova; A. D. Alpatskaya; A. V. Korotkikh; M. O. Dzhanelidze; M. A. Rusakova; E. U. Kharchilava; M. V. Sulimenko; V. A. Lutsenko; R. V. Sultanov; F. R. Alizada; E. O. Meleshin; et al. (Российский кардиологический журнал, 2022)
Aim. To demonstrate the first Russian computer program (carotidscore.ru) for risk stratification of postoperative complications of carotid endarterectomy (CE).Material and methods. The present study is based on the analysis of a multicenter Russian database including 25812 patients after CE operated on from January 1, 2010 to April 1, 2022. The following types of CE were implemented: conventional CE with patch angioplasty — 6814 patients; eversion CE — 18998 patients. Following postoperative complications were assessed during the study: death, stroke, myocardial infarction (MI), composite endpoint (death + stroke + MI).Results. During inhospital postoperative period, 0,18% of participants died, while 0,14% had MI, 0,35% — stroke. The composite endpoint was recorded in 0,68%. For each factor present in patients, a predictive coefficient was estimated. The predictive coefficient was considered as a numerical parameter reflecting the strength of the effect of each factor on the development of postoperative complications. Based on this equation, predictive coefficients were calculated for each factor present in patients in our study. The total contribution of these factors was reflected as a percentage and denoted the risk of postoperative complications with a minimum of 0% and a maximum of 100%. On the basis of obtained calculations, a CarotidSCORE program was created. Its graphical interface is based on the QT framework. It is possible not only to estimate the risk of a complication, but also to save all data about a patient in JSON format. The CarotidSCORE program contains 47 patient parameters, including clinical, demographic, anamnestic and angiographic characteristics. It makes it possible to choose one of the four CE types, which will provide an accurate stratification of the complication risk for each of them.Conclusion. CarotidSCORE (carotidscore.ru) may determine the probability of postoperative complications in patients undergoing CE.